Activity-Based Profiling Reveals a Regulatory Link between Oxidative Stress and Protein Arginine Phosphorylation. Issue 8 (18th August 2016) - Fuhrmann, Jakob; Subramanian, Venkataraman; Kojetin, Douglas J.; Thompson, Paul R.
Summary: Protein arginine phosphorylation is a recently discovered modification that affects multiple cellular pathways in Gram-positive bacteria. In particular, the phosphorylation of arginine residues by McsB is critical for regulating the cellular stress response. Given that the highly efficient protein arginine phosphatase YwlE prevents arginine phosphorylation under non-stress conditions, we hypothesized that this enzyme negatively regulates arginine phosphorylation and acts as a sensor of cell stress. To evaluate this hypothesis, we developed the first suite of highly potent and specific SO3 -amidine-based YwlE inhibitors. With these protein arginine phosphatase-specific probes, we demonstrated that YwlE activity is suppressed by oxidative stress, which consequently increases arginine phosphorylation, thereby inducing the expression of stress-response genes, which is critical for bacterial virulence. Overall, we predict that these novel chemical tools will be widely used to study the regulation of protein arginine phosphorylation in multiple organisms. Graphical Abstract: Highlights: Generation of SO3 -amidine based protein arginine phosphatase inhibitors Development of an activity-based affinity probe (ABAP) for arginine phosphatases The ABAP probes reveal that YwlE activity is negatively regulated by oxidative stress Inhibition of YwlE activity increases McsB-mediated arginine phosphorylation Abstract : Protein arginine phosphorylation is an elusive protein modification that is involved in cell signaling. Based on the development of selective chemical probes, Fuhrmann et al. expose the molecular basis for how cells regulate protein arginine phosphorylation under oxidative stress conditions.